Use of objective methods to determine the holding time of hold elements on still rings - Lehmann, T.; Winter, A.; Seemann-Sinn, A.; Naundorf, F. (Science of Gymnastics Journal, 2021)
The duration of holding elements represents a critical factor for judging routines on the still rings in artistic gymnastics. Athletes can be penalized with non-recognition of an element if the hold time is too short. Dynamometric and kinematic measuring methods offer the possibility to provide support to judges in evaluating the duration of the hold time. In this study a dynamometric method with two different variants (dms10 and dms5) as well as a kinematic method (kms) based on a trained neural network were presented and examined with regard to their agreement with judges` evaluations when determining the hold time. To check the agreement, a) the percentage agreement and b) the interrater reliability were calculated using Cohen's kappa (k). The two dynamometric methods showed a percentage agreement of 83.5% (dms10) and 51.7% (dms5) with the hold time evaluation by judges. The percentage agreement of the kms was 38.8%. The interrater reliability showed for the dms10 a moderate (k = 0.58) and for the dms5 a fair (k = 0.23) agreement, while the kms showed a poor (k = 0.02) match. The results supported dms10 for its possible use as a practicable and reliable method to assist judges in evaluating hold times on the still rings. Dms5 and kms (in the current development stage) were not suitable as means of judges` support.